Evaluation of drug use habits and rational drug use of persons registered to primary health care - Deniz, Serdar; Oğuzöncül, Ayşe Ferdane; Bentli, Recep (My University, 2018)
Wrong or unnecessary use of medications seriously affects public health. The aim of this study is to evaluate the drug use habits and rational drug use among people aged 15 and over who are registered to family health centers in Akçadağ district of Malatya. The population of the study consists of 21659 people in the 15 and older age group registered in the family physicians in Akçadağ district of Malatya. The frequency of rational drug use was determined as 46.6%, the margin of error was 5% and the confidence interval was 95% and the minimum sample size was calculated as 376. It was aimed to reach a total of 420 people. Not be using drugs other than doctor’s advice, using drugs as recommended time by the doctor and using drugs as recommended dose by the doctor, all of the features were evaluated as ‘’rational drug using’’. The mean age was 42.84 ± 16.39. Of the group, 50.2% were males and 7.1% were illiterate. It was determined that those who had difficulty in meeting health expenses accounted for 9.3% of the group, 61.9% of them were generally in good health, 36.0% had a long-term or chronic disease. Those who did not use the medication without a doctor’s recommendation were 31.4%, those who used the drug in the amount recommended by the doctor, 55.7%, and 54.5% of the patients who were taking the drug at the recommended time. The prevalence of rational drug use was 23.8%. Rational drug use was associated with gender and educational status (p <0.05). The frequency of rational drug use is low. The importance of rational drug use to each individual in society should be explained in accordance with the individual characteristics.
Keywords: Genel ve Dahili Tıp; Sağlık Politikaları ve Hizmetleri; Farmakoloji ve Eczacılık; İstatistik ve Olasılık